2013
DOI: 10.1073/pnas.1305579110
|View full text |Cite
|
Sign up to set email alerts
|

Testicular volume is inversely correlated with nurturing-related brain activity in human fathers

Abstract: Despite the well-documented benefits afforded the children of invested fathers in modern Western societies, some fathers choose not to invest in their children. Why do some men make this choice? Life History Theory offers an explanation for variation in parental investment by positing a trade-off between mating and parenting effort, which may explain some of the observed variance in human fathers' parenting behavior. We tested this hypothesis by measuring aspects of reproductive biology related to mating effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 48 publications
6
104
0
Order By: Relevance
“…For example, during the first few months of the postpartum period, both new mothers and fathers exhibit structural growth in brain regions including the striatum and prefrontal cortex that support warm and supportive parenting behaviors (Kim et al 2010b;. Sensitive neural activations, particularly for one's own baby, have also been consistently identified among new mothers and fathers during these same periods, when parents and infants establish long-lasting emotional relationships (Barrett and Fleming 2011;Mascaro et al 2013;Musser et al 2012). At the same time, parents in poverty are far more vulnerable to development of postpartum depression (Boury et al 2004; U.S. Department of Health and Human Services 2002;Walker et al 2002), and it is possible that as the result of depression and the stress of living in poverty, they are also more likely to exhibit abusive or harsh parenting (Sedlak and Broadhurst 1996;Widom and Nikulina 2012).…”
Section: Suggestions For Policy and Interventionsmentioning
confidence: 99%
“…For example, during the first few months of the postpartum period, both new mothers and fathers exhibit structural growth in brain regions including the striatum and prefrontal cortex that support warm and supportive parenting behaviors (Kim et al 2010b;. Sensitive neural activations, particularly for one's own baby, have also been consistently identified among new mothers and fathers during these same periods, when parents and infants establish long-lasting emotional relationships (Barrett and Fleming 2011;Mascaro et al 2013;Musser et al 2012). At the same time, parents in poverty are far more vulnerable to development of postpartum depression (Boury et al 2004; U.S. Department of Health and Human Services 2002;Walker et al 2002), and it is possible that as the result of depression and the stress of living in poverty, they are also more likely to exhibit abusive or harsh parenting (Sedlak and Broadhurst 1996;Widom and Nikulina 2012).…”
Section: Suggestions For Policy and Interventionsmentioning
confidence: 99%
“…At the same time, it has been found that masculine facial traits increase both perceived dominance and negative attributions of male faces including decreased quality as a parent (e.g., Boothroyd et al 2007;Borras-Guevara et al 2017;Penton-Voak et al 1999;Perrett et al 1998). Indeed, high levels of testosterone have been linked to undesirable social traits such as aggression and decreased paternal investment (e.g., Booth and Dabbs 1993;Mascaro et al 2013;Pollet et al 2011). Thus, it has been suggested that women face a trade-off between less masculine but more agreeable, investing long-term partners and men whose more masculine appearance would indicate good male condition, but at the same time less socially desirable traits (e.g., Penton-Voak et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore possible that increased investment in ejaculates could trade off with traits that directly enhance female fitness, such as nuptial gift size or provision of parental care (e.g., Simmons et al 1993). For example, male secondary sexual traits can trade off with paternal care provision (Smith 1995) and such trade-offs could be mediated by testosterone production (Wingfield et al 1990;Mascaro et al 2013).…”
Section: Ejaculate Variationmentioning
confidence: 99%